(untitled) (Web of Teachers: Inderscience Research, 2025)
Promoting self-assessment skills in intermediate learners is an essential strategy for enhancing foreign language acquisition. Self-assessment allows learners to reflect on their strengths and areas for improvement, fostering autonomy and motivation in the learning process. This article discusses practical approaches to implementing self-assessment in foreign language classrooms, particularly using English language materials. By introducing clear self-assessment criteria and tools such as rubrics and reflective questionnaires, teachers can help learners evaluate their speaking, writing, listening, and reading abilities. The article also highlights the contributions of various experts in the field, emphasizing the importance of self-regulation and self-assessment for developing cognitive skills and fostering learner independence. Additionally, integrating peer and teacher feedback further enhances the accuracy and effectiveness of self-assessment. The article concludes that self-assessment is a powerful tool for promoting successful language learning and should be a central aspect of language instruction.